2009
DOI: 10.1634/stemcells.2008-0366
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Activity of Eltrombopag (SB-497115), an Oral, Nonpeptide Thrombopoietin Receptor Agonist

Abstract: Eltrombopag is a first-in-class, orally bioavailable, small-molecule, nonpeptide agonist of the thrombopoietin receptor (TpoR), which is being developed as a treatment for thrombocytopenia of various etiologies. In vitro studies have demonstrated that the activity of eltrombopag is dependent on expression of TpoR, which activates the signaling transducers and activators of transcription (STAT) and mitogen-activated protein kinase signal transduction pathways. The objective of this preclinical study is to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
205
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(216 citation statements)
references
References 29 publications
9
205
1
1
Order By: Relevance
“…The ultimate responses to eltrombopag are similar to those observed with endogenous TPO with stimulation of transcription through STAT-based and megakaryocytespecific promoters [37]. However, studies have reported some differences in activation of downstream targets of the TPO receptor between eltrombopag and human recombinant TPO (hrTPO).…”
Section: Eltrombopagmentioning
confidence: 70%
See 3 more Smart Citations
“…The ultimate responses to eltrombopag are similar to those observed with endogenous TPO with stimulation of transcription through STAT-based and megakaryocytespecific promoters [37]. However, studies have reported some differences in activation of downstream targets of the TPO receptor between eltrombopag and human recombinant TPO (hrTPO).…”
Section: Eltrombopagmentioning
confidence: 70%
“…However, treatment with eltrombopag did not result in a significant change in differentiation nor maturation characteristics of the granulocytic/monocytic or the erythrocytic lineages, indicating that eltrombopag preferentially acts on progenitor and precursor cells harbouring megakaryocytic potential [38]. Thus, eltrombopag is a true agonist of the human TPO receptor that is able to act on megakaryocytes and their progenitors in a manner similar to TPO with the potential to induce differentiation and proliferation of megakaryocytes and ultimately relieve thrombocytopenia [37].…”
Section: Eltrombopagmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Eltrombopag does not compete with thrombopoietin for binding to c-MPL, since it binds in the membrane-spanning region outside the ligand-binding pocket of c-MPL, and it activates signaling through JAK-STAT (Janus-associated kinase-signal transducers and activators of transcription) and MAPK (mitogen-activated protein kinase) pathways. 22 Eltrombopag may stimulate hematopoiesis by non-competitive activation of c-MPL, despite elevated thrombopoietin levels, and it may activate signaling in a way that is distinct from that of thrombopoietin.…”
Section: Discussionmentioning
confidence: 99%